Subducted lithosphere under South America from multifrequency p wave tomography - Mohammadzaheri, A; Sigloch, K; Hosseini, K; Mihalynuk, MG (American Geophysical Union, 2021)
We analyze mantle structure under South America in the DETOX-P1 seismic tomography model, a global-scale, multifrequency inversion of teleseismic P waves. DETOX-P1 inverts the most extensive data set of broadband, waveform-based traveltime measurements to date, complemented by analyst-picked traveltimes from the ISC-EHB catalog. The mantle under South America is sampled by ∼665,000 cross-correlation traveltimes measured on 529 South American broadband stations and on 5,389 stations elsewhere. By their locations, depths, and geometries, we distinguish four high-velocity provinces under South America, interpreted as subducted lithosphere (“slabs”). The deepest (∼1,800–1,200 km depth) and shallowest (<600 km) slab provinces are observed beneath the Andean Cordillera near the continent’s northwest coast. At intermediate depths (1,200–900 km, 900–600 km), two slab provinces are observed farther east, under Brazil, Bolivia and Venezuela, with links to the Caribbean. We interpret the slabs relative to South America’s paleo-position over time, exploring the hypothesis that slabs sank essentially vertically after widening by viscous deformation in the mantle transition zone. The shallowest slab province carries the geometric imprint of the continental margin and represents ocean-beneath-continent subduction during Cenozoic times. The deepest, farthest west slab complex formed under intra-oceanic trenches during late Jurassic and Cretaceous times, far west of South America’s paleo-position adjoined to Africa. The two intermediate slab complexes record the Cretaceous transition from westward intra-oceanic subduction to eastward subduction beneath South America. This geophysical inference matches geologic records of the transition from Jura-Cretaceous, extensional “intra-arc” basins to basin inversion and onset of the modern Andean arc ∼85 Ma.